An orally available, brain-penetrant CAMKK2 inhibitor reduces food intake in rodent model. Issue 10 (1st June 2018) - Price, Daniel J.; Drewry, David H.; Schaller, Lee T.; Thompson, Brian D.; Reid, Paul R.; Maloney, Patrick R.; Liang, Xi; Banker, Periette; Buckholz, Richard G.; Selley, Paula K.; McDonald, Octerloney B.; Smith, Jeffery L.; et al.
Graphical abstract: Abstract: Hypothalamic CAMKK2 represents a potential mechanism for chemically affecting satiety and promoting weight loss in clinically obese patients. Single-digit nanomolar inhibitors of CAMKK2 were identified in three related ATP-competitive series. Limited optimization of kinase selectivity, solubility, and pharmacokinetic properties were undertaken on all three series, as SAR was often transferrable. Ultimately, a 2, 4-diaryl 7-azaindole was optimized to afford a tool molecule that potently inhibits AMPK phosphorylation in a hypothalamus-derived cell line, is orally bioavailable, and crosses the blood–brain barrier. When dosed orally in rodents, compound 4 t limited ghrelin-induced food intake.